Zikir Dan Ketenangan Jiwa: Kajian Psikologis - Abdul Rozak Ali Maftuhin; Syamsurizal Yazid (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Dhikr is the practice of remembering Allah by mentioning His name, either verbally or in the heart, as well as through physical actions or deeds with the aim of drawing closer to Him. This study uses a qualitative approach with a library research method. The data sources for this research are books, journals, and research reports related to dhikr and its benefits, both from an Islamic perspective and from a psychological standpoint. The objective of this research is to describe the role of dhikr as a medium for Islamic spiritual counseling to bring peace of mind through the integration of Islamic values from a psychological perspective. The findings of this study indicate that dhikr brings many benefits, including gaining forgiveness from Allah, calming the heart and soul, avoiding heedlessness, and receiving abundant rewards from Allah. In terms of psychology, dhikr can promote relaxation, enhance mental focus, help overcome life challenges, boost motivation, influence physical health, support harmonious social relationships, and improve the effectiveness of healing for patients undergoing therapy or treatment.